2017
DOI: 10.1016/j.bmcl.2017.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Natural abenquines and synthetic analogues: Preliminary exploration of their cytotoxic activity

Abstract: In this study, we explore the cytotoxic activity of four natural abenquines (2a-d) and fourteen synthetic analogues (2e-j and 3a-h) against a panel of six human cancer cell lines using a SRB assay. It was found that most of the compounds revealed higher levels of cytotoxic activities than naturally occurring abenquines. The analogues carrying ethylpyrrolidinyl and ethylpyrimidinyl with either an acetyl group (2h-i) or a benzoyl group (3f-g), were the most potent against all human cancer cell lines and displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Over the last years or so, the use of 1,4-quinone, an important source of natural products, has enabled the design of efficient and active molecules with improved pharmacological properties in the search of new molecules with cytotoxic activity [ 11 , 12 , 13 , 14 , 15 , 16 ]. The 1,4-quinone and 1,4-naphthoquinone moieties are well-represented in bioactive natural structures and their anticancer effects, including anti-colorectal cancer properties, have been documented in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years or so, the use of 1,4-quinone, an important source of natural products, has enabled the design of efficient and active molecules with improved pharmacological properties in the search of new molecules with cytotoxic activity [ 11 , 12 , 13 , 14 , 15 , 16 ]. The 1,4-quinone and 1,4-naphthoquinone moieties are well-represented in bioactive natural structures and their anticancer effects, including anti-colorectal cancer properties, have been documented in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of analogues (4e−h) involved the reaction of an equivalent amount of the different amines and quinone 3a. 34,40 Further modification on the abenquine structure involved replacement of the acetyl moiety by the bulkier group benzoyl (Figure 2). To obtain the analogues 5a−h, the required intermediate quinone 3b was prepared employing the same chemical procedure used for the synthesis of 3a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Initially the amino acid moiety was substituted with different amines, maintaining the acetamide group as part of the abenquine scaffold. The preparation of analogues ( 4e – h ) involved the reaction of an equivalent amount of the different amines and quinone 3a . , …”
Section: Resultsmentioning
confidence: 99%
“…The second one is the production of the semiquinones by a one‐electron reduction (Castro, Mariani, Panek, Eleutherio, & Pereira, ; Gutierrez, ; Widhalm & Rhodes, ). Recent years have witnessed respectable progress in the development of biologically active 1,4‐quinones based on natural compounds (Johnson‐Ajinwo et al, ; Nain‐Perez et al, ; Nain‐Perez, Barbosa, Maltha, & Forlani, ). 1,4‐Quinone moiety constitutes the fundamental framework of versatile natural or synthetic quinone molecules such as plastoquinone (PQ) (Kawamukai, ), mitomycin C (Begleiter, ; Sugiura, ), and thymoquinone (Collett et al, ; El‐Dakhakhany, ; Glamoclija et al, ) since they have extensively found ample and numerous applications in the design and synthesis of pharmacologically active agents exhibiting a wide range of biological activities such as anticancer (Wellington, ; Wellington, Kolesnikova, Nyoka, & McGaw, ), antibacterial (Janeczko, Demchuk, Strzelecka, Kubinski, & Maslyk, ; Jordao et al, ), antifungal (Ryu, Oh, Choi, & Kang, ; Shrestha et al, ), anti‐HIV (Alfadhli et al, ; Ilina et al, ), antimalarial (Carneiro et al, ; Pingaew et al, ), antiallergic (Lien, Huang, Teng, Wang, & Kuo, ), antiinflammatory (Tandon, Chhor, Singh, Rai, & Yadav, ), antithrombotic (Jin, Ryu, Moon, Cho, & Yun, ; Yuk et al, ), lipoxy‐genase inhibitory (Richwien & Wurm, ), human monoamine oxidase (MOA) inhibitory (Cerqueira, Netz, Diniz, do Canto, & Follmer, ), and antiplatelet activities (Lien et al, ; Yuk et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Abenquines are natural products containing amino acid residues and the first total synthesis of abenquines has been achieved by Nain‐Perez and coworkers (Nain‐Perez, Barbosa, Maltha, & Forlani, ). Nain‐Perez et al have shown abenquines and their analogs’ cytotoxicity activities against six human tumor cell lines and nonmalignant mouse fibroblasts (Nain‐Perez, Barbosa, Rodriguez‐Hernandez, Kramell, et al, ). Additionally, the same group has also used this class of structures as a model for the synthesis of new herbicides targeting photosynthesis (Nain‐Perez, Barbosa, Maltha, Giberti, & Forlani, ).…”
Section: Introductionmentioning
confidence: 99%